2018
DOI: 10.1002/jqs.3079
|View full text |Cite
|
Sign up to set email alerts
|

Late Quaternary glaciations in the Cogarbu valley, Bhutanese Himalaya

Abstract: This study investigates the late Quaternary glacial history of the Cogarbu valley on the northern slopes of the Bhutanese Himalaya using 10Be surface exposure dating. Five major glacial events were constrained based on 28 10Be exposure ages. The equilibrium line altitude (ELA) of the oldest and most extensive glacial event (M5–M9) is ∼489 m lower than the present, followed by four other events (M4, M3, M2 and M1) with ELA depressions of ∼452, ∼200, ∼76 and ∼42 m, respectively. The exposure ages of the oldest g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 64 publications
(138 reference statements)
0
14
0
Order By: Relevance
“…In “dip‐coating,” the top layer is formed by immersing the substrate in an appropriate polymer solution . Some studies have investigated the effects of PDMS coating conditions, such as concentration of coating solution, solvent type, and number of coatings on performance of the prepared composite membranes . However, the effect of variation in dip time for coating the PDMS solution has not been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…In “dip‐coating,” the top layer is formed by immersing the substrate in an appropriate polymer solution . Some studies have investigated the effects of PDMS coating conditions, such as concentration of coating solution, solvent type, and number of coatings on performance of the prepared composite membranes . However, the effect of variation in dip time for coating the PDMS solution has not been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…1; Fig. 2a-2c; Marzeion et al, 2012;Maussion et al, 2019;Peng et al, 2019Peng et al, , 2020Parkes, et al, 2020). Our study revealed that the summer temperature plays a dominant role in controlling glacier changes at suborbital-scale.…”
Section: Climate-forcing Mechanismsmentioning
confidence: 57%
“…The ongoing debate about the pattern of glacier evolution during the LIA is, in part, resulted from an imperfect understanding on how to cross validate observation with simulation, what the contribution of individual glacier to regional glacier evolution is, and how climate change drives glacier evolution (Goosse et al, 2018;Carrivick et al, 2019;Peng et al, 2019Peng et al, , 2020. Based on previous works, this study improves the understanding of the pattern of LIA glacier changes in Bhutanese Himalaya (BH; Fig.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…PDMS is extensively used in various applications due to its low glass transition temperature ( T g = −123 °C), as well as its adequate thermal, chemical and oxidative stability . These properties are useful in preparing the silicone rubber membrane, but the PDMS should be crosslinked to stabilize it against flow into the support.…”
Section: Methodsmentioning
confidence: 99%